2022
DOI: 10.3390/ijerph192013382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Complications of COVID-19 Illness among a Diverse Sample of Children by MIS-C Status

Abstract: Most pediatric COVID-19 cases are asymptomatic; however, a small number of children are diagnosed with multisystem inflammatory syndrome in children (MIS-C), a rare but severe condition that is associated with SARS-CoV-2 infection. Persistent symptoms of COVID-19 illness in children diagnosed with/without MIS-C is largely unknown. A retrospective EHR review of patients with COVID-19 illness from one pediatric healthcare system to assess the presence of acute (<30 days) and chronic (≥30, 60–120, and >120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…After MIS-C, it is also possible to run into the typical disturbances of long COVID [ 7 ]. In the study of Messiah et al, 27% of children with MIS-C examined reported chronic long COVID symptoms, with the three most reported symptoms being tiredness, headache, and difficulty thinking [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After MIS-C, it is also possible to run into the typical disturbances of long COVID [ 7 ]. In the study of Messiah et al, 27% of children with MIS-C examined reported chronic long COVID symptoms, with the three most reported symptoms being tiredness, headache, and difficulty thinking [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cardiac involvement is frequent, and some patients may have residual heart lesions, a progression of coronary involvement even after discharge and the onset or progression of arrhythmic disorders after the initial diagnosis [ 6 ]. After MIS-C, it is also possible to run into the typical disturbances of long COVID [ 7 ]. All these conditions can affect the well-being of young patients and impose the need for long-term follow-up [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, results of the prospective study by Morello et al showed that age more than 10 years, prexisting conditions and hospitalization during the acute phase due to severity of disease increased the risk of developing LC of about 4, 2 and 3 times, respectively ( Morello et al, 2023 ). Moreover, recent data indicate that persistent clinical manifestations after COVID-19 are more common in children with MIS-C. At this regard, Messiah et al reported that 26.9% of children that have suffered from MIS-C reported chronic LC compared to 15.3% of those without Messiah et al (2022) .…”
Section: Presently Available Information On Long Covid In Childrenmentioning
confidence: 99%
“…These studies, conducted with information from Electronic Health Recordings (EHR), also used different approaches in selecting the control groups and focus on specific objectives: health care utilization [ 21 ], prevalence and incidence of symptoms after 12 weeks of acute disease and persistence of previous symptoms [ 22 ], mortality and use of health care services [ 23 ]. In addition, most studies did not include children [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%